PERSEPSI HARGA, PERSEPSI MEREK, PERSEPSI NILAI, DAN KEINGINAN PEMBELIAN ULANG JASA CLINIC KESEHATAN (STUDI KASUS ERHA CLINIC SURABAYA) - Ike Kusdyah (Institute of Research and Community Outreach - Petra Christian University, 2012)
Price and brand perception has an influence on intents to repurchase mediated by perceived value. The results of the analysis of 112 women respondents using Structural Equation Modelling (SEM) obtained results that: (1) positive effect on price perception of perceived value, (2) positive effect on brand perception of perceived value, (3) perceptions of the price effect the desire repeat purchases, (4) does not affect the perception of the brand re-purchase desire; (5) Perceived value has a positive effect on repeat purchase desire.